Pott’s puffy tumor and orbital abscess - Unusual cause - da Costa, Liliana Filipa Invencio; Acevedo Ortiz, Laura; Ruiz Giner, Antonio; Galindo Ortego, Xavier Francisco (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2023)
Introduction: Pott's Puffy tumor is a subperiosteal abscess that typically arises from frontal osteomyelitis. It can also originate from sinus tumors, with squamous cell carcinoma being the most frequent histological type. Clinical case: A 72-year-old male presented with orbital and frontal cellulitis. Subsequent CT and MRI scans revealed the presence of a mass in both frontal sinuses, which led to bone erosion and the formation of an abscess in the frontal region, known as Pott's Puffy tumor. The abscess was drained, and a biopsy confirmed a monoclonal plasmablastic lymphoma. Following the completion of an intravenous antibiotic regimen, the patient underwent chemotherapy, which resulted in the remission of the tumor Discussion: Plasmablastic lymphoma is an unusually aggressive subtype of large B-cell non-Hodgkin's lymphoma that primarily affects mucous membranes, with a predilection for the oral cavity. Due to its low incidence, there is currently no established treatment approach for this condition.